Project finance : the guide to financing telecommunications projects - Woodhouse, Tim ed. (Euromoney Pub. LondonGB, 1997)
Looks at the trend towards privatisation; telecoms regulatory issues; and key project issues. Examines project documentation and provides privatisations case studies. Lists selected carrier privatisations 1980-1996.